The Effect Of Using Skimming And Scanning Technique In Reading Comprehension - David Hutahaean; Melda V.R. Munthe (Jurnal Ilmu Sosial dan Humaniora, 2026)
In real life reading is often part of series of activities, including locating texts and presenting material in oral and in written. Reading is an activity of process of transferring or decoding form the written to oral form. But in other side, reading is not easy as what people think because it is not only requires reading a series of sentences, but also it needs the reader to understand the content of the reading text and its purpose. People who want to know how to read the passage or text or sentences well, they must know how to learn about it.these things are started from students. Many students do not know how to read well, so this is that the researcher want to do and solve the problems. The students can understand an English text but they cannot comprehend what is in the content of the text that they have read. Reading proficiency depends on the ability of the students to recognize words quickly and effortlessly. If the students have difficulty to recognize the words, the students used too much processing capacity to read individually words, which interferes with their ability to comprehend what is read. Students had the problem on reading comprehension because they did not understand what the content of the text. To solve the problem in teaching reading, the researcher used skimming and scanning strategy to improve students’ reading comprehension. Basically there are some technique in reading but Scanning is quickly searching for some particular piece of information in the text.it is sure that will make the student be better than before in reading. And the other purpose of this research to produce a good book teaching for reading especially the technique in scanning.it hopes that will changes the characters of student not only student but to people who read the book be well. The target of outher of this research besides to produce the book teaching, it is will be published in journal that get legal licence.Finally This research aims to find the effect of student in using skimming and scanning in reading comprehension ability